In Vivo Characterization of a Red Light-Activated Vasodilation: A Photobiomodulation Study - Keszler, Agnes; Lindemer, Brian; Broeckel, Grant; Weihrauch, Dorothee; Gao, Yan; Lohr, Nicole L. (Frontiers in Physiology, 2022)
Nitric oxide dependent vasodilation is an effective mechanism for restoring blood flow to ischemic tissues. Previously, we established an ex vivo murine model whereby red light (670 nm) facilitates vasodilation via an endothelium derived vasoactive species which contains a functional group that can be reduced to nitric oxide. We investigated this vasodilator in vivo by measuring blood flow with Laser Doppler Perfusion imaging in mice. The vasodilatory nitric oxide precursor was analyzed in plasma and muscle with triiodide-dependent chemiluminescence. First, a 5-10 min irradiation of 670 nm (50 mW/cm2) produced maximal vasodilation. The nitric oxide precursor in the irradiated quadriceps tissue decreased from 123±18 pmol/g tissue by both intensity and duration of light treatment to an average of 90±17 pmol/g tissue, while stayed steady (137±21 pmol/g tissue) in unexposed control hindlimb. Second, blood flow remained elevated 30 min after termination of the light exposure. The nitric oxide precursor content significantly increased by 50% by irradiation then depleted in plasma, while remained stable in the hindlimb muscle. Third, to mimic human peripheral artery disease, an ameroid constrictor was inserted on the proximal femoral artery of mice and caused a significant reduction of flow. Repeated light treatment for 14 days achieved steady and significant increase of perfusion in the constricted limb. Our results strongly support 670 nm light can regulate dilation of conduit vessel by releasing a vasoactive nitric oxide precursor species and may offer a simple home-based therapy in the future to individuals with impaired blood flow in the leg.